1997
DOI: 10.1084/jem.186.5.645
|View full text |Cite
|
Sign up to set email alerts
|

Self Antigens Expressed by Solid Tumors Do Not Efficiently Stimulate Naive or Activated T Cells: Implications for Immunotherapy

Abstract: Induction and maintenance of cytotoxic T lymphocyte (CTL) activity specific for a primary endogenous tumor was investigated in vivo. The simian virus 40 T antigen (Tag) expressed under the control of the rat insulin promoter (RIP) induced pancreatic β-cell tumors producing insulin, causing progressive hypoglycemia. As an endogenous tumor antigen, the lymphocytic choriomeningitis virus (LCMV) glycoprotein (GP) was introduced also under the control of the RIP. No significant spontaneous CTL activation against GP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

13
177
2
1

Year Published

1998
1998
2002
2002

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 275 publications
(193 citation statements)
references
References 42 publications
13
177
2
1
Order By: Relevance
“…This phenomenon was observed even in TILN, in which melan-A-expressing tumor cells were effectively adjacent to melan-A CTL precursors (patients M29 and M30). It therefore seems likely that these patients are in a state analogous to the peripheral ignorance proposed from some animal tumor models (35,36), in which tumor-specific CTL are present both in the circulation and the lymphoid tissue, but have not been primed by tumor Ag. As noted above, unprimed CTL were seen even in the circulation of patients who had managed to prime at least a proportion of their melan-A-specific CTL.…”
Section: Priming Of Melan-a-specific Ctl Precursors Is Often Weak In mentioning
confidence: 94%
See 1 more Smart Citation
“…This phenomenon was observed even in TILN, in which melan-A-expressing tumor cells were effectively adjacent to melan-A CTL precursors (patients M29 and M30). It therefore seems likely that these patients are in a state analogous to the peripheral ignorance proposed from some animal tumor models (35,36), in which tumor-specific CTL are present both in the circulation and the lymphoid tissue, but have not been primed by tumor Ag. As noted above, unprimed CTL were seen even in the circulation of patients who had managed to prime at least a proportion of their melan-A-specific CTL.…”
Section: Priming Of Melan-a-specific Ctl Precursors Is Often Weak In mentioning
confidence: 94%
“…Expression libraries of tumor cDNAs showed that the target of these CTL was melan-A, a lineage-specific molecule also expressed on normal melanocytes (2,3). The dominant HLA-A2-restricted epitope of melan-A originally appeared to be melan-A [27][28][29][30][31][32][33][34][35] (AAGIGILTV) (4), but subsequent experiments showed melan-A 26 -35 (EAAGIGILTV) is also recognized by CTL, and binds better to HLA-A2 (5). Many laboratories have since found it relatively easy to generate CTL specific for this epitope from HLA-A2 ϩ melanoma patients (6,7), and it therefore seemed that melan-A 26/7-35 might be the most commonly recognized epitope among all the known targets of melanoma Ag-specific CTL (6).…”
mentioning
confidence: 99%
“…A comparable minimal effect of a single vaccination had been shown in the case of a LCMV-GP -positive insulinoma. 108 If, however, mice were immunized either with a high dose of 2Â10 6 pfu of LCMV-WE causing a prolonged and widely spreading infection with long -term CTL activation, or alternatively by repeated injections of LCMV-GP -expressing DC or MC -GP in 2 -to 5 -day intervals for 3 weeks, most tumor fragments failed to grow further and eventually disappeared completely ( Fig 4F ). Thus, an antigen -driven prolonged CTL response is needed to reject peripheral tumors, initially for maximal expansion of the CTLp frequency and later to maintain the specific CTLs activated and able to lyse target cells.…”
Section: Cancer Gene Therapymentioning
confidence: 99%
“…The CD28 Ϫ/Ϫ mice were originally obtained from T. Mak (Ontario Cancer Institute, Toronto, Canada) (19), and the RIP-LCMV-gp ϩ transgenic line was provided by P. Ohashi (Ontario Cancer Institute) (12). Briefly, PCR amplifications were performed on tail-DNA for 35 cycles as described (10,11,19,20). In some instances, the CD28 phenotype was confirmed by CD28 staining of PBL as described (21).…”
Section: Micementioning
confidence: 99%